Joana Roque de Pinho's Zoom transcript, Kenya, July 26, 2021 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2021)
To have access to the research data file, please contact: Joana Roque de Pinho: roquedepinho.joana@gmail.com
Keywords: Arid regions; East Africa; Maasai (African people); Herders; Tourism; Livestock; Pastoralist; Conservancy; Lockdown; Kenya; COVID-19 Pandemic